New Bis(dithiocarbamate) Ligand for Complex Formation; Synthesis, Spectral Analysis and Bacterial Activity - Yousif, Enaam I.; Hasan, Hasan A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A range of macrocyclic dinuclear metal (II) dithiocarbamate-based complexes are reported. The preparation of complexes was accomplished from either mixing of the prepared ligand with a metal ion or through a template one-pot reaction. The preparation of the bisamine precursor was achieved through several synthetic steps. The free ligand; potassium 2,2’-(biphenyl-4,4’-diylbis(azanediyl))bis(1-chloro-2-oxoethane-2,1diyl)bis(cyclohexylcarbamodithioate) (L) was yielded from the addition of CS2 to a bis-amine precursor in KOH medium.A variety of analytical and physical methods were implemented to characterise ligand and its complexes. The analyses were based on spectroscopic techniques (FTIR, UV-Vis, mass spectroscopy and 1H, 13C-NMR spectroscopy), melting points, elemental analysis, thermal properties, magnetic susceptibility and conductance. The analytical and physical techniques confirmed the formation of macrocyclic complexes of the general formulae [M(L)]2 (M= MnII, CoII, NiII, CuII, ZnII and CdII). The proposed structure around MnII, CoII, ZnII and CdII is a tetrahedral, while NiII and CuII complexes adopt square planar geometries. The prepared compounds were screened against four bacterial species (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus stubtilis). The anti-bacterial test indicated that the complexes are more active against these bacterial strains, compared with the free ligand.